2021
DOI: 10.1016/j.jds.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients suffered from burning mouth syndrome and persistent idiopathic facial pain using Japanese version PainDETECT questionnaire and depression scales

Abstract: Background/purpose Various questionnaires have been validated as methods for screening of neuropathic pain, but none have been established for the orofacial region. Although chronic pain and depression are likely to comorbid, few studies have examined the relationship between orofacial chronic pain and depression. Therefore, we evaluated the potential of the Japanese Version of PainDETECT as an assessment tool for neuropathic pain associated with burning mouth syndrome (BMS) and persistent idiopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Moreover, the median and IQR of the PD‐Q score of the BMS patients in this sample was 8 [4.75–11.2] and only in 3 patients (7.5%) could the pain be considered as neuropathic (PD‐Q > 19). This result is in accordance with the study of Boku et al 39 on 29 patients with BMS where the authors concluded that the pain in fewer than 15% could include neuropathic pain elements. These results are in contrast with the study of Lopez‐Jornet et al, 18 on 33 BMS patients, where the pain was considered neuropathic in 21% of patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, the median and IQR of the PD‐Q score of the BMS patients in this sample was 8 [4.75–11.2] and only in 3 patients (7.5%) could the pain be considered as neuropathic (PD‐Q > 19). This result is in accordance with the study of Boku et al 39 on 29 patients with BMS where the authors concluded that the pain in fewer than 15% could include neuropathic pain elements. These results are in contrast with the study of Lopez‐Jornet et al, 18 on 33 BMS patients, where the pain was considered neuropathic in 21% of patients.…”
Section: Discussionsupporting
confidence: 92%
“…23 In addition, these scales have shown their positive correlation with the psychological profile and QoL. Instead, in accordance with the study of Boku et al, 39 the PD-Q seems not to be a suitable tool for the evaluation of pain in BMS, if different tools are available, because our results confirm that the nature of pain may be nociceptive rather than neuropathic.…”
Section: Ta B L E 5 (Continued)supporting
confidence: 76%
See 2 more Smart Citations
“…In clinical terms, the mucosa appears healthy without any obvious lesions, and this condition may be accompanied by xerostomia and/or dysgeusia. The sensation is recurrent on a daily basis, for more than 2 h/day, and for more than 3 months [ 1 , 2 ]. The intensity of which ranges from moderate to severe, with it increasing throughout the day, although it tends to be absent at night.…”
Section: Introductionmentioning
confidence: 99%